Why Refugees Rebel: Towards a Comprehensive Theory of Refugee Militarization. (8th March 2013) - Lebson, Mike
Abstract: Militarization by refugees can have problematic outcomes. It can undermine the sovereignty and stability of the host state, perpetuate a transnational conflict and obstruct international efforts to resolve it, and present difficulties in the provision of humanitarian assistance to needy populations. Existing literature privileges structural explanations for militarization while neglecting the agency, interests and internal politics of refugee groups. In this paper, I offer a comprehensive theory of refugee militarization that emphasizes the importance of endogenous factors, including political and economic motivations, in the context of broader structural factors, including political opportunities and resource mobilization, mediated by the presence of militancy entrepreneurs. This theory helps integrate the motivation of refugees, and the discursive framing used by militancy entrepreneurs to mobilize them, with capacity for militant activity. The need for case studies and specific policy recommendations for host states, non‐governmental organizations and international stakeholders are discussed.